The Discursive Impact of Disinformation on Journalism - Parzianello, Geder (Žurnalistikos tyrimai, 2025)
Contemporary discourses, particularly within journalism, often claim to represent multiple facets of reality. However, many of these representations are misleading, fictional, or entirely detached from empirical facts. Public opinion is not only influenced by traditional media and digital platforms but is actively constructed through rhetorical and discursive strategies that obscure factual accuracy. These mechanisms restrict the epistemological function of information and undermine the autonomy of communication professionals, thus compromising the public’s ability to discern truth. In today’s global context, marked by increasingly complex political, economic, and military conflicts, the instrumental propaganda, distinguished as journalism, has become more prevalent like a phenomenon of further intelligence technologies. Segments of journalism are increasingly shaped by such discursive formations. This essay employs discourse analysis to examine these dynamics, by highlighting how these factors foster the gradual erosion of professional journalism. Our argument advances the view that the most pressing threat does not arise from technology or Artificial Intelligence per se, but rather from the ethical challenges that emerge in the management and circulation of information. In this regard, the central risk lies in disinformation becoming embedded as a discursive practice in journalism.